2016
DOI: 10.1111/fare.12179
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Family Characteristics on Problem Behaviors in a Sample of High‐Risk Caribbean Adolescents

Abstract: Drawing on the social development model, the authors examine family risk and protective factors thought to influence problem behaviors among adolescents. They estimate the impact of family risk and protective factors on a variety of antisocial and health risk behaviors. Data are drawn from a sample of nearly 2,500 adolescents attending high‐risk schools in Trinidad and Tobago, a developing nation in the eastern Caribbean. The findings show that certain family risk factors play a more consistent role in shaping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…A small but growing number of research studies on youth violence in Caribbean countries have reported similar results with respect to significant risk and protective factors discussed above (Blum & Ireland, 2004;Katz & Fox, 2010;Maguire & Fishbein, 2016;Williams, 2013). Maguire and Fishbein (2016) found that a history of family antisocial behavior and parent attitudes favorable toward antisocial behavior were stronger risk factors for problem behaviors of youth in Caribbean counties (Trinidad and Tobago), though significant family protective factors were not found.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…A small but growing number of research studies on youth violence in Caribbean countries have reported similar results with respect to significant risk and protective factors discussed above (Blum & Ireland, 2004;Katz & Fox, 2010;Maguire & Fishbein, 2016;Williams, 2013). Maguire and Fishbein (2016) found that a history of family antisocial behavior and parent attitudes favorable toward antisocial behavior were stronger risk factors for problem behaviors of youth in Caribbean counties (Trinidad and Tobago), though significant family protective factors were not found.…”
mentioning
confidence: 76%
“…Maguire and Fishbein (2016) found that a history of family antisocial behavior and parent attitudes favorable toward antisocial behavior were stronger risk factors for problem behaviors of youth in Caribbean counties (Trinidad and Tobago), though significant family protective factors were not found. In addition, Katz and Fox (2010) and Williams (2013) identified some significant factors affecting youth violence or gang involvement at the school level, including peer association, lack of positive interactions with teachers, the opportunity for prosocial involvement, and low commitment to school.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Gang violence imprisons some residents in their neighborhoods and limits children's opportunities for recreation in community spaces. It also exposes children and adolescents (as well as other residents) to extreme levels of trauma, thus potentially limiting their growth and development and perpetuating the cycle of violence (Maguire and Fishbein, 2016;Singer, Anglin, Song, & Lunghofer, 1995). For many young men growing up in the communities we examined, the inability to move about freely (for fear of crossing gang boundaries) as well as biased hiring practices, make it difficult to leave the community and to find legitimate work.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, rather than the modular packaging of functions that theorists sometimes associate with a type of intelligence or cognitive ability, EF are thought to access multiple streams of information processing and experience and potentially interact with all available mental resources in choosing responses and attaining goals. Given these kinds of influences on behavior, EF impairments during development (due to either acquired illness, injury, or developmental disruption) can have far-reaching and disabling effects in everyday life (Eslinger, Flaherty-Craig, & Chakara, 2013;Maguire & Fishbein, 2016). Hinnant et al (2013) argued that EF are the convergence of higher cognitive abilities under situation-specific circumstances that facilitate control functions.…”
Section: Executive Functions the Prefrontalmentioning
confidence: 99%